2023
DOI: 10.3390/agronomy13030904
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Pulp Biomass Utilization on Coffee Production and Its Impact on Energy Saving, CO2 Emission Reduction, and Economic Value Added to Promote Green Lean Practice in Agriculture Production

Abstract: The global market’s sustainability demand for coffee as a result of environmental concerns has influenced coffee producers to practice green coffee production. The efforts to improve the environmental performance of coffee production should also consider the other sustainability aspects: energy and economics. Using a green fertilizer from agricultural biomass can lower carbon dioxide (CO2) emissions since the cultivation process, which is directly impacted by fertilizer use, has been identified as an environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…There are some points to highlight related to the social impacts of the three different coffee industry management systems in rural areas: (1) The existence of the coffee processing industry in rural areas generated the most positive impact to the local community, specifically in the impact on the local employment in all types of management systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some points to highlight related to the social impacts of the three different coffee industry management systems in rural areas: (1) The existence of the coffee processing industry in rural areas generated the most positive impact to the local community, specifically in the impact on the local employment in all types of management systems.…”
Section: Discussionmentioning
confidence: 99%
“…The increased coffee demand has promoted massive coffee production at upstream and downstream levels [1]. The intensive agricultural industry production substantially depletes the natural resources and causes environmental damage [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was reported that processing 1 kg of coffee beans would produce 1 kg of waste (43.2% skin and pulp, parchment 6.1%, and 11.8% mucilage and soluble sugar). It is also indicated that the production of coffee pulp can be calculated from the number of coffee beans produced (Orrego et al 2018;Rahmah et al 2023).…”
Section: Introductionmentioning
confidence: 99%